Mindsets about remote work predict employee well-being in home office: Evidence from the COVID-19 pandemic - Howe, Lauren C.; Menges, Jochen I. (2020)
ABSTRACT During the COVID-19 pandemic, millions of employees worldwide transitioned to remote work. As remote work continues to characterize the post-crisis world of work, it is imperative to understand predictors of employee adjustment to remote work. The current research explores the extent to which individuals hold a fixed mindset about remote work (e.g., that a person either is or is not suited to remote work and this cannot be changed) and tested how this mindset shaped remote worker well-being during the coronavirus lockdown. In a longitudinal five-week study of 113 employees working remotely in Switzerland, we find that employees who endorsed a more fixed mindset about remote work experienced more negative emotion and reduced positive emotion during remote work. Further, the increased negative emotion prompted by fixed mindsets was associated with lesser perceived productivity among these employees. We conclude that encouraging employees to view remote work as a skill that can be learned and developed could help employees thrive in the new world of work. Keywords remote work, telecommuting, employee well-being, productivity, mindsets ABOUT THE AUTHOR/S Lauren C. Howe Howe University of Zurich lauren.howe@business.uzh.ch Dr. Lauren C. Howe is a postdoctoral scholar working with Prof. Jochen Menges at the Chair of Human Resource Management and Leadership at the University of Zurich. Her research examines the critical role of beliefs, expectations, and social relationships in organizational contexts and illustrate how considering their influence can lead to novel insights. Her website is here: http://www.laurenchowe.com/ Jochen I. Menges University of Zurich jochen.menges@uzh.ch Professor Jochen Menges holds the Chair of Human Resource Management and Leadership at the Department of Business Administration at the University of Zurich. He received his doctoral degree in management from the University of St. Gallen, spent a year at the Graduate School of Arts and Science at Yale University, and completed undergraduate and graduate degrees in psychology at the University of Heidelberg. He also works as a Lecturer in Organizational Behaviour at Judge Business School at the University of Cambridge and has previously served as the Chair of Leadership and HRM at WHU – Otto Beisheim School of Management in Düsseldorf. Professor Menges’s research focuses on the social dynamics between leaders and followers, and on the role of emotions and motivation in organizational life. He studies how leaders can successfully inspire people to pursue collective goals and how people can work together in ways that contribute to their productivity and well-being. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).